2005
DOI: 10.1080/13550280590952790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for human immunodeficiency virus–associated neurocognitive impairment, 1996 to 2002: Results from an urban observational cohort

Abstract: To assess prevalence and risk factors for human immunodeficiency virus (HIV)-related neurocognitive impairment (NCI), the authors performed a 7-year survey in the period 1996 to 2002. A total of 432 patients were examined. HIV-related NCI was diagnosed in 238 patients (55.1%), meeting the HIV dementia (HIV-D) criteria in 45 (10.4%). The prevalence of both NCI and HIV-D did not change significantly during the study period. Compared with patients without NCI, patients with NCI were older (40.4 versus 38.2 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 21 publications
6
77
2
2
Order By: Relevance
“…In many countries, highly active antiretroviral therapy (HAART) has been successfully implemented, leading to greatly decreased mortality and prolonged course of infection. However even in the current era of treatment, the brain remains a target for damage and dysfunction: in spite of HAART lowering the overall incidence of CNS problems, the prevalence of infected individuals with CNS neurocognitive disorders has remained the same or possibly increased (2)(3)(4)(5). This may be due in part to the fact that many HIV therapeutics do not cross the blood-brain barrier in sufficient quantity (6), as well as the now-prolonged course of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, highly active antiretroviral therapy (HAART) has been successfully implemented, leading to greatly decreased mortality and prolonged course of infection. However even in the current era of treatment, the brain remains a target for damage and dysfunction: in spite of HAART lowering the overall incidence of CNS problems, the prevalence of infected individuals with CNS neurocognitive disorders has remained the same or possibly increased (2)(3)(4)(5). This may be due in part to the fact that many HIV therapeutics do not cross the blood-brain barrier in sufficient quantity (6), as well as the now-prolonged course of infection.…”
Section: Introductionmentioning
confidence: 99%
“…These factors might contribute to the lower prevalences of DSP and HAND compared with other recruited cohorts or studies conducted in neurology clinics. 8,9,11,23 Unlike DSP and HAND, the prevalence and incidence of several neurologic disorders herein remain unchanged in the cART era. The incidence of mononeuropathy was consistent during the study period, likely because immunologic and virologic variables were less robust risk factors for this disorder.…”
Section: Ratio Of Aids-related Death In Patients With Hiv/aids With Nmentioning
confidence: 99%
“…The differences in the prevalence of neurocognitive impairment in HIV-infected individuals in different studies lie in the population selection and study design. Tozzi et al 8 reported a 55.1% prevalence of HIV-related neurocognitive impairment in 432 patients undergoing their first neuropsychological tests in an institute which provides care to more than 3,500 HIV-infected individuals. A recent study of HAND prevalence in HIV-infected individuals with suppressed viremia by Simioni et al 23 using questionnaire and neuropsychological tests estimated the prevalence of HAND at 69%; however, the majority of patients with HAND had asymptomatic neurocognitive impairment.…”
Section: Ratio Of Aids-related Death In Patients With Hiv/aids With Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for HAND include current or past low CD4 cell count, 6,[15][16][17][18] advanced age, 15,16,19 coinfection with hepatitis C virus, 18,20 insulin resistance or diabetes, 19 and cardiovascular risk factors. 21 Advanced immune suppression, either current or historical, and older age are strong risk factors for HAND, being reported in most published studies.…”
Section: Risk Factorsmentioning
confidence: 99%